2016
DOI: 10.1016/j.brq.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Board of director's effectiveness and the stakeholder perspective of corporate governance: Do effective boards promote the interests of shareholders and stakeholders?

Abstract: This paper analyzes whether effective boards of directors in addressing shareholder interests also prove to be effective in guaranteeing the interests of the rest of the firm's stakeholders. We measure board effectiveness based on the shareholder perspective, and test whether it is valid for the stakeholder perspective. The novelty of this paper precisely lies in its approach, given that it considers both perspectives of corporate governance at a time. Using the transparency of sustainability reports as a prox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
2
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 92 publications
(135 reference statements)
2
69
2
9
Order By: Relevance
“…The establishment of governance structures related to CSR, such as a CSR committee, emphasizes the significant relationship between corporate governance and CSR (Garcia-Torea et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The establishment of governance structures related to CSR, such as a CSR committee, emphasizes the significant relationship between corporate governance and CSR (Garcia-Torea et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The relationships can provide channels for communication with, and access to support from, external organizations [37] and other kinds of stakeholders. This perspective makes it necessary to revisit the concept of the effectiveness of a company's board from a shareholder perspective to assess its validity in stakeholder theory [38]. It has been suggested that the stakeholder perspective of CG should be linked to CSP [39].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Regarding the board characteristics with an impact on CSR reporting, researchers have explored the effects of the presence of insiders (Mohd‐Ghazali, ), independent directors (Cabeza‐García, Sacristán‐Navarro, & Gómez‐Ansón, ), institutional directors (Jones, Makri, & Gomez‐Mejia, ; Samara & Berbegal‐Mirabent, ), and female directors (Frías‐Aceituno, Rodríguez‐Ariza, & García‐Sánchez, ) on CRS policies. According to Garcia‐Torea, Fernandez‐Feijoo, and de la Cuesta (), board attributes determine a board's effectiveness in performing tasks involving monitoring or making decisions, among other things. Thus, board characteristics are effective corporate governance mechanisms if they enable a board to carry out its duties.…”
Section: Introductionmentioning
confidence: 99%